2017
DOI: 10.1073/pnas.1615072114
|View full text |Cite
|
Sign up to set email alerts
|

TRAIL-death receptor endocytosis and apoptosis are selectively regulated by dynamin-1 activation

Abstract: Clathrin-mediated endocytosis (CME) constitutes the major pathway for uptake of signaling receptors into eukaryotic cells. As such, CME regulates signaling from cell-surface receptors, but whether and how specific signaling receptors reciprocally regulate the CME machinery remains an open question. Although best studied for its role in membrane fission, the GTPase dynamin also regulates early stages of CME. We recently reported that dynamin-1 (Dyn1), previously assumed to be neuron-specific, can be selectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 41 publications
4
74
0
1
Order By: Relevance
“…PLCγ1 has also been proposed to regulate endocytosis by acting as a guanyl exchange factor for dynamin1 in neuronal cells (Choi et al. , 2004), and dynamin1 selectively regulates the clathrin-mediated endocytosis of tumor necrosis factor–related apoptosis-inducing ligand (TRAIL)-death receptor (DR) (Reis et al. , 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PLCγ1 has also been proposed to regulate endocytosis by acting as a guanyl exchange factor for dynamin1 in neuronal cells (Choi et al. , 2004), and dynamin1 selectively regulates the clathrin-mediated endocytosis of tumor necrosis factor–related apoptosis-inducing ligand (TRAIL)-death receptor (DR) (Reis et al. , 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, calcineurin and dynamin1 were dispensable for the internalization of EGFR (Figure 4A and Supplemental Figure 3, A and B), suggesting that Ca 2+ -dependent control of clathrin-mediated endocytosis in RPE cells does not rely on acute dephosphorylation of endocytic proteins such as dynamin1 by calcineurin, a phenomenon that regulates the clathrin-mediated endocytosis of TRAIL/DR (Reis et al. , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…68,69 Further comparative analysis of the CME of distinct receptors has found differences in requirements for lipids, 70 auxiliary proteins, 68,[71][72][73][74] and regulation by intracellular calcium. 75 Collectively these studies have revealed that understanding the systematic regulation of CME may be best accomplished by complementing assays that monitor the traffic of individual cargo receptors with systematic study of CCPs.…”
Section: Heterogeneity Of Molecular Assemblies and Organelles In Mementioning
confidence: 99%
“…These cell type differences might reflect the immortalization process (45) or the strong dependence on supplemental EGF for growth and maintenance of the HBEC cell line (see Methods). Alternatively, they may reflect cell-type and/or cargo-dependent differences in endocytic machinery as previously observed for death receptor-dependent endocytosis (46).…”
Section: Resultsmentioning
confidence: 79%
“…Hyperactivity of EGFR signaling at the cell surface is a common feature among different types of cancers and widely considered advantageous for tumor progression (46). Why then, would ERK1/2 activation downstream of EGFR activate a mechanism that enhances CCP initiation and EGFR endocytosis and suppresses EGFR proliferative and migratory signaling?…”
Section: Discussionmentioning
confidence: 99%